Social and Cultural Context in the Formation of Student Morals in Islamic Educational Environments - Widodo, Hadi; Siyamsih, Dwi (PT. Anagata Sembagi Education, 2024)
This study aims to analyze the role of social and cultural contexts in the formation of students' morals in Islamic education. The formation of morals is a key aspect of Islamic education, which not only provides religious knowledge but also nurtures noble character. The study employs a Systematic Literature Review (SLR) to collect and analyze data from various relevant sources on moral education within social and cultural contexts. The literature reviewed is drawn from academic databases and accredited articles discussing Islamic education, morals, and the influence of social and cultural factors on character development. The findings indicate that social and cultural environments significantly impact students' moral development. Students in positive environments, such as those raised in families that instill Islamic values and interact with supportive peers, tend to exhibit better behaviors, including honesty, responsibility, and compassion. In contrast, students exposed to negative environments, such as harmful peer groups or unhealthy media influences, are more vulnerable to deviant behavior. The study also highlights that local cultural values, such as respect for parents and politeness, strengthen moral education. This research underscores the importance of collaboration between families, schools, and communities, and suggests integrating local cultural values into Islamic moral education for a more effective and relevant approach.